The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/dmso.s262760
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bacterial Profiles and Their Associated Factors of Urinary Tract Infection and Detection of Extended Spectrum Beta-Lactamase Producing Gram-Negative Uropathogens Among Patients with Diabetes Mellitus at Dessie Referral Hospital, Northeastern Ethiopia</p>

Abstract: Purpose: To determine the bacterial profile with its associated risk factors and to identify extended spectrum beta-lactamase producing Gram-negative bacterial uropathogens among diabetic patients at Dessie Referral Hospital, Northeastern Ethiopia. Materials and Methods: A hospital-based cross-sectional study was conducted from May to September 2018. A total of 336 diabetic patients were included using a simple random sampling technique. A structured questionnaire was used to collect socio-demographic and risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 28 publications
6
13
5
Order By: Relevance
“…(4%); E. faecalis and Streptococcus spp. each (1.3%), and this study was similar to the previous studies of Kibret and Abera [ 13 ] and Alemu et al [ 14 ]. However, the observed high proportion of E .…”
Section: Resultssupporting
confidence: 92%
“…(4%); E. faecalis and Streptococcus spp. each (1.3%), and this study was similar to the previous studies of Kibret and Abera [ 13 ] and Alemu et al [ 14 ]. However, the observed high proportion of E .…”
Section: Resultssupporting
confidence: 92%
“…This finding is contrary with other studies, which reported E. coli as predominant bacterial isolate (27,42,45,40). However, E. coli was the most predominant isolate among gram negative bacterial isolates with an isolation rate of 8 (14.0%), which is supported by most of the studies conducted in Hawassa (42) Metu (27) Ghana (16),Nigeria (42.3) (27, 37, 40, 42).…”
Section: Discussioncontrasting
confidence: 99%
“…Total number of 380 estimated blood samples was included as a sample for the study which was calculated using a single proportion formula 5 keeping 95% confidence level and 5% confidence interval. The blood samples were collected by a well-trained nurse and Pediatrician by using aseptic technique.…”
Section: Methodsmentioning
confidence: 99%